2005
DOI: 10.1185/030079905x59148
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D inadequacy in Scottish adults with non-vertebral fragility fractures

Abstract: This study confirms almost universal vitamin D inadequacy among 548 elderly patients admitted to hospital with hip fracture, regardless of whether a threshold of 50 nmol/L or 70 nmol/L was used. However, among a prospective subset of 50 patients with clinical fragility fractures, especially those with non-hip fractures, the prevalence of inadequacy was substantially lower. It may be that vitamin D represents a correctable risk factor for fragility fracture in the elderly, possibly specifically for the hip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 19 publications
5
49
0
Order By: Relevance
“…The levels of Vitamin D-insufficiency and of profound Vitamin D-deficiency are of concern, but are not dissimilar to those of other recent UK studies. Gallacher et al [11] found the incidence of Vitamin D-insufficiency was 97% (<70 nmol/l) in white adults (>60 years) in Scotland. Hamson et al [12] in a cross-section of the general adult population (20-40 years) in Leicester found that 3% of white and 55% of Gujarati men and women were profoundly Vitamin D-deficient (<5 ng/ml).…”
Section: Discussionmentioning
confidence: 98%
“…The levels of Vitamin D-insufficiency and of profound Vitamin D-deficiency are of concern, but are not dissimilar to those of other recent UK studies. Gallacher et al [11] found the incidence of Vitamin D-insufficiency was 97% (<70 nmol/l) in white adults (>60 years) in Scotland. Hamson et al [12] in a cross-section of the general adult population (20-40 years) in Leicester found that 3% of white and 55% of Gujarati men and women were profoundly Vitamin D-deficient (<5 ng/ml).…”
Section: Discussionmentioning
confidence: 98%
“…A review of serum vitamin D levels in the fracture population reveals that 62%-91% of hip fracture patients had unequivocal vitamin D insufficiency, with serum levels less than 50 nmol/L. 25,[35][36][37][38][39] In patients with any fragility fracture, the mean serum vitamin D level ranged from 42.5 to 63 nmol/L. 16,18,24,35,36 The higher mean serum 25-hydroxyvitamin D levels observed in our study may be due to 15% (46 of 308) of these patients having been diagnosed and treated for osteoporosis before their index fracture and some patients having vitamin D and calcium supplementation initiated before their assessment at the MBDC.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly people are at greater risk of vitamin D deficiency because of risk factors such as (1) suboptimal sunlight exposure and lower cutaneous synthesis of vitamin D, (2) reduced dietary intake of D 2 (ergocalciferol) and D 3 (cholecalciferol), (3) impaired intestinal absorption, and (4) impaired hydroxylation in the liver and kidneys 1 Vitamin D deficiency is common in elderly patients in Western countries, especially in the early spring due to reduced cutaneous synthesis during winter months, 5,6 in housebound individuals, 7 and in medical inpatients. 8 The prevalence of vitamin D deficiency is even higher in elderly patients with fragility fractures (varying from 55% to 91.6% 6,[9][10][11][12] ).…”
Section: Introductionmentioning
confidence: 99%